Isu-isu Kontemporer Ekonomi Pancasila - M. Dawam Raharjo (Unisia, 2004)
Reformation and it's process shows us that Indonesia has lost it's direction in maintaining economical situation. Pancasila economic system, is still become our economic paradigm, referring to chapter 33 of amended constitution of 1945. Koperasi (corporation) as the pillar for Pancasila economic system, still unable to answer economic challenges for the future. The unclear direction of economic development, actually is caused by the ignorance of people toward ideas which is relevant to be grown in the context of Pancasila economic system. With only catching the surface of this economic system, impossible for Indonesian people to think deeply and maturely toward this economic system itself. Thus, this is the real question which must be addressed In the future coming.